Deliberative Collaborative Governance as a Democratic Reform to Resolve Wicked Problems and Improve Trust - Weymouth, R.; Hartz-Karp, Janette (Southern Cross University, Centre for Policy Research, 2015)
A persistent and increasing governance challenge has appeared in the last several decades in mature democracies at all levels from national to local that stems from declining trust levels in government by citizens. This lack of trust leads to multiple policy implementation problems for governments, city and regional local governments alike, especially those facing complex sustainability issues - wicked problems. A process known as deliberative collaborative governance that enables more meaningful public participation in issues that matter, with greater decision-making transparency, accountability and perceived legitimacy, has been demonstrably effective in helping to redress the governance gap. National and international examples of deliberative collaborative governance over the last two decades illustrate the potential of this method to close the governance gap. A four year action research case study in a regional town in Western Australia is used to illustrate how deliberative collaborative governance has positively affected the implementation of local government policy and operations including their responses to wicked problems, and reduced the governance gap.